PENDALAMAN MATERI SEJARAH ABU BAKAR ASH-SHIDDIQ DAN UMAR BIN KHATTAB PADA TOPIK KHULAFA’ AL-RASYIDIN DI KELAS VI MADRASAH IBTIDAIYAH - Suharti, Sri; Daulay, Haidar Putra; Dahlan, Zaini (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
Islamic Cultural History is one of the lessons at the Madrasah Ibtidaiyah level. In the subject of Islamic Cultural History in Grade VI there are discussion topics related to Khulafa 'Al-Rasyidin. Among Khulafa 'Al-Rashidin, the four were Abu Bakr Ash-Siddiq, Umar bin Khattab, Uthman bin Affan and Ali bin Abi Talib. In this discussion, it discusses the historical material of Abu Bakr Ash-Siddiq and Umar bin Khattab as an in-depth study of material in class VI Madrasah Ibtidaiyah. The material on the leadership of two Khulafa 'Al-Rasyidin described can add insight or deepening of the historical material of Abu Bakr Ash-Siddiq and Umar bin Khattab for educators in Class VI Madrasah Ibtidaiyah in the subject of Islamic Cultural History. With the deepening of this material, it is hoped that Educators will find it easier to explain and describe the discussion related to the historical material of Abu Bakr Ash-Shiddiq and Umar bin Khattab in Class VI Madrasah Ibtidaiyah so that it is easy for Class VI students to understand Madrasah Ibtidaiyah.